Method for manufacturing a thermoelectric conversion element
The described method addresses the challenges of achieving high-density and scalable thermoelectric conversion elements by using a skutterudite-type thermoelectric conversion material powder mixed with a Mn and Sb compound sintering aid, resulting in enhanced thermoelectric performance and mass production feasibility.
Patent Information
- Application Number
- JP2022510456
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-23
- Filing Date
- 2021-03-22
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-03-22
AI Technical Summary
Existing methods for manufacturing thermoelectric conversion elements face challenges in achieving high density and scalability while maintaining thermoelectric properties, with issues such as insufficient relative density due to pressure limitations and potential oxidation leading to performance deterioration.
A manufacturing method involving the mixing of skutterudite-type thermoelectric conversion material powder with a sintering aid containing a compound of Mn and Sb, followed by sintering, which facilitates high-density bulk production and maintains thermoelectric performance.
The method achieves a high-density thermoelectric conversion element with excellent mass production capabilities while preserving thermoelectric properties, as evidenced by improved power factor and reduced electrical resistance.
Smart Images

Figure 0007655309000001 
Figure 0007655309000002 
Figure 0007655309000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoelectric conversion element that directly converts thermal energy into electrical energy. [Background technology]
[0002] In recent years, in order to reduce energy consumption, it has been considered to recover exhaust heat from heat sources such as boilers, incinerators, and automobiles as electricity. In particular, thermoelectric conversion modules that can efficiently recover electrical energy using thermoelectric conversion elements that can directly convert thermal energy into electrical energy by the Seebeck effect have attracted attention. The most practical materials are Bi2Te3-based compounds, which are mainly used in the temperature range from room temperature to about 200°C, but with the aim of becoming the next popular material, materials that exhibit high thermoelectric performance in various temperature ranges are being searched for. In particular, inorganic materials such as silicides, Pb-Te, skutterudite, Si-Ge, and Heusler systems have been shown to exhibit high thermoelectric properties in the temperature range of 300°C or higher, and are being actively researched.
[0003] A well-known inorganic thermoelectric conversion module is one in which an N-type element with electrons as carriers and a P-type element with holes as carriers are arranged in a π-shape, with one end connected by an electrode. The elements used in π-shaped modules are rectangular or cubic, with dimensions of several mm to 1 cm, so a technology is required to efficiently manufacture bulk material elements of several mm in size. The commonly used manufacturing method is to melt the raw materials, pulverize the material with the desired composition, and then pressure sinter the powder. Pressure sintering is a method in which sintering and molding are performed simultaneously by compressing while heating. Methods that have been adopted include hot pressing, HIP (Hot Isostatic Pressing), and spark plasma sintering (SPS), which simultaneously applies mechanical pressure and pulse current heating.
[0004] For example, Patent Document 1 discloses a skutterudite compound Ce 0.2 Co 3.95 Mn 0.05 Sb 12The paper discloses a thermoelectric conversion element using the above, and a manufacturing method thereof, in which metal raw materials containing Ce, Co, Mn, and Sb are placed in a quartz tube, sealed in a vacuum, melted at 1100°C for 12 hours, quenched in water, and the resulting ingot is heat-treated at 800°C for 120 hours, and the resulting powder is sintered by SPS at 600°C for 5 minutes under a pressure of 50 MPa.
[0005] Patent Document 2 discloses a thermoelectric conversion material having an average crystal grain size of 50 nm or less and a relative density of 85% or more, and a method for producing the thermoelectric conversion material, in which a finely pulverized powder is prepared and sintered or solidified under a pressure of 0.5 GPa or more and 10 GPa or less. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2013 / 009430 [Patent Document 2] International Publication No. 2004 / 049464 Summary of the Invention [Problem to be solved by the invention]
[0007] The method of Patent Document 1 has a problem that when the size is increased for mass production, the relative density of the thermoelectric conversion element is likely to be insufficient due to insufficient pressure, etc. On the other hand, when a finely pulverized powder is obtained as in Patent Document 2, the specific surface area is large, so oxidation is likely to progress in the pre-sintering stage, and when a thermoelectric conversion element is obtained using this, there is a problem that the thermoelectric performance of the thermoelectric conversion element is likely to decrease.
[0008] An object of the present invention is to provide a method for producing a thermoelectric conversion element that is suitable for high density and has excellent mass productivity while maintaining thermoelectric properties. [Means for solving the problem]
[0009] The method for producing a thermoelectric conversion element of the present invention includes the steps of: A step of mixing a powder of a skutterudite-type thermoelectric conversion material containing Sb with a sintering aid containing a compound of Mn and Sb to obtain a mixture; sintering the mixture; and The present invention is characterized by comprising:
[0010] In addition, the compound consisting of Mn and Sb was found to be Mn by XRD. 1.1 It is preferable that a peak of at least one of the crystal structures of Sb and Mn2Sb is observed.
[0011] In addition, the mixture preferably contains 10 mass % or less of the sintering aid based on the total amount of the thermoelectric conversion material and the sintering aid.
[0012] The thermoelectric conversion material powder preferably contains Yb and Co.
[0013] The thermoelectric conversion material powder preferably contains Ce and Fe. Effect of the Invention
[0014] According to the present invention, it is possible to provide a method for manufacturing a thermoelectric conversion element that is suitable for high density and has excellent mass productivity while maintaining thermoelectric properties. [Brief description of the drawings]
[0015] [Figure 1] 1 is a flowchart showing a method for manufacturing a thermoelectric conversion element. [Diagram 2] 4 is a flowchart showing a process for preparing a thermoelectric conversion material powder. [Diagram 3] 4 is a flowchart showing a step of mixing a thermoelectric conversion material powder with a sintering aid and associated steps. [Figure 4] 1 is a flowchart showing a sintering process. [Diagram 5] 1 is a comparison of (a) electrical resistance, (b) Seebeck coefficient, and (c) power factor between Example 1 and Comparative Example 1. [Figure 6]1A is a photograph of a cross section of Example 1 observed with an SEM at a magnification of 500 times, and FIG. 1B is a photograph of a cross section of Example 1 observed with an SEM at a magnification of 2000 times. [Figure 7] 1A is a photograph of a cross section of Comparative Example 1 observed with an SEM at a magnification of 500 times, and FIG. 1B is a photograph of a cross section of Comparative Example 1 observed with an SEM at a magnification of 2000 times. [Figure 8] 1A is a photograph of a cross section of Example 3 observed with an SEM at a magnification of 2000 times, and FIG. 1B is a photograph of a cross section of Comparative Example 3 observed with an SEM at a magnification of 2000 times. [Figure 9] FIG. 4 is a diagram showing the relationship between the density of a thermoelectric conversion element and the sintering pressure. [Figure 10] This is the result of HAADF-STEM-EDX line analysis of the grain boundaries of a thermoelectric conversion element. [Figure 11] 1 shows the correlation between the pressure sintering pressure and density in Example 10 and Comparative Example 4. [Figure 12] 1 shows the correlation between the pressure sintering pressure and density in Examples 11, 12, and Comparative Example 5. [Figure 13] 1 shows the correlation between the pressure sintering pressure and density in Example 14 and Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] An embodiment of the manufacturing method of the thermoelectric conversion element of the present invention will be described below. As shown in Fig. 1, the manufacturing method of the thermoelectric conversion element of this embodiment includes a step of preparing a skutterudite-type thermoelectric conversion material powder containing Sb (S1: thermoelectric conversion material powder preparation step), a step of mixing the thermoelectric conversion material powder with a sintering aid containing a compound of Mn and Sb to obtain a mixture (S2: sintering aid mixing step), and a step of sintering the mixture (S3: sintering step). Note that the skutterudite-type thermoelectric conversion material powder containing Sb may be purchased, and the step of preparing the skutterudite-type thermoelectric conversion material powder containing Sb (S1: thermoelectric conversion material powder preparation step) may be omitted.
[0017] First, the process of preparing the thermoelectric conversion material powder shown in FIG. 2 will be described below. In the present invention, the thermoelectric conversion material contains Sb and has a skutterudite crystal structure. For example, CoSb3-based materials containing Yb, CoSb3-based materials, CoSb3-based materials containing Ce, and FeSb3-based materials containing Ce can be mentioned. For example, Yb 0.3 Co4Sb 12 The metal raw materials are weighed out according to the composition formula of the desired thermoelectric conversion material (S1-1: raw material weighing step). At this time, since antimony (Sb) has a high vapor pressure, it may be weighed out slightly more, for example, 1 to 3 mass%, in consideration of the trace evaporation during heating. In addition, raw materials that are easily oxidized, such as cerium (Ce), are preferably weighed out in an inert atmosphere. The weighed metal raw materials are melted and solidified in a non-oxidizing atmosphere in an electric furnace or a high-frequency furnace (S1-2: melting and solidifying step). As the non-oxidizing atmosphere, an inert gas (argon, nitrogen N2, etc.) may be used, or the raw materials may be vacuum sealed in a quartz tube, and liquid quenching and solidification may be used in the melting and solidification. Melting and liquid quenching and solidification may be performed continuously in the same furnace, or the raw materials may be melted to prepare a mixed ingot, and the ingot may be heated and melted again, and liquid quenching and solidification may be performed. For example, in the case of high-frequency melting, it is confirmed that the entire material is in a liquid phase and the molten metal is stirred by high-frequency, and after holding for several tens of seconds to several minutes, the molten metal is poured into a mold to form an ingot. In the liquid quenching and solidification, a method of pouring the molten metal onto a rotating roll at about 100°C or less (room temperature or water cooling may be used), a method of spraying the molten metal from a crucible with a nozzle by gas pressure, etc. may be applied. The sample obtained by the liquid rapid solidification is in the form of a ribbon, and its thickness is preferably in the range of 1 μm to 1 mm. The rapidly solidified ribbon-shaped sample is in a state where skutterudite crystals, amorphous mixtures, intermetallic compounds other than skutterudite, etc. are mixed. In order to increase the amount of skutterudite crystals, the sample may be heat-treated at a predetermined temperature in a non-oxidizing atmosphere (S1-3: heat treatment step). Whether or not the skutterudite type is the main phase of the thermoelectric conversion material can be confirmed by XRD (X-ray Diffraction). The skutterudite material obtained by heat-treating the ribbon-shaped sample may be pulverized under an inert atmosphere (S1-4: pulverization step). The pulverization method may be, for example, a hammer mill, a jet mill, a ball mill, a crusher equipped with a mortar, or the like. The average particle size may be determined by wet laser diffraction, and for example, D50 is desirably 0.5 μm to 100 μm, preferably 1 μm to 80 μm, and more preferably 2 μm to 50 μm. After pulverization, a method of classifying fine powder and coarse powder with a sieve may be used as appropriate.
[0018] Next, the step of mixing the thermoelectric conversion material powder with a sintering aid containing a compound of Mn and Sb to obtain a mixture (S2-4: mixing step of thermoelectric conversion material powder and sintering aid) shown in FIG. 3 will be described. The thermoelectric conversion material powder and the sintering aid may be sufficiently mixed and dispersed so that densification proceeds in the sintering step, and may be, for example, milled using media, mixed in a mortar, or rotary mixed using a V-type mixer. The sintering aid used will be described below. The sintering aid in this embodiment contains a compound of Mn and Sb, and by mixing and sintering such a sintering aid with the thermoelectric conversion material powder, an effect of facilitating sintering is obtained. Here, the compound of Mn and Sb is, for example, a target compound obtained by weighing out pure manganese and pure antimony in an atomic ratio range of Mn / Sb=0.2 to 3 (S2-1: weighing sintering aid step) and dissolving (S2-2: melting and solidifying step). The auxiliary component thus obtained is, for example, a mixture of MnSb and Sb when the atomic ratio Mn / Sb is 1 or less, MnSb when the atomic ratio Mn / Sb is around 1, and a mixture of MnSb and Mn2Sb when the atomic ratio Mn / Sb>1.2. When Mn / Sb>2, Mn2Sb is mixed with excess Mn. In other words, a compound consisting of Mn and Sb is a compound in which the ratio of Mn to Sb is approximately 1 (hereinafter, Mn 1.1 It can be said that the alloy contains a compound consisting of Mn and Sb (hereinafter, sometimes written as Mn2Sb), or a compound in which Mn is approximately 2 to Sb (hereinafter, sometimes written as Mn2Sb). Whether or not the alloy contains a compound consisting of Mn and Sb can be confirmed by XRD, and from the alloy phase diagram of Mn and Sb, Mn 1.1Since either Sb or Mn2Sb is a stable alloy, a compound containing either was used. That is, a compound consisting of Mn and Sb was used as a sintering aid, and Mn was found to be Mn by XRD. 1.1 It is sufficient that a peak of at least one of the crystal structures of Sb and Mn2Sb is observed.
[0019] In addition, in the melting process (S2-2: melting and solidifying process) which is a process before the mixing process, either an electric furnace or a high-frequency furnace may be used. In addition, a liquid quenching and solidifying method may be used, in which the material is melted in a liquid quenching and solidifying device equipped with a metal roll, and the molten metal is poured onto a rotating roll to rapidly solidify and obtain a ribbon-shaped sample, which makes the subsequent crushing process easier. Next, the ingot-shaped material obtained by melting and solidifying may be crushed into powder (S2-3: crushing process). The powder works effectively as a sintering aid when it is well dispersed and coordinated on the surface of the thermoelectric conversion material powder. Whether the thermoelectric conversion material and the sintering aid are uniformly dispersed can be determined by observing the distribution of Mn in the aid and elements such as Co and Fe in the thermoelectric conversion material, for example, using SEM-EDX (Scanning Electron Microscope Energy Dispersive X-ray Spectroscopy). The amount of sintering aid added is preferably such that the amount of thermoelectric conversion material is not significantly reduced relative to the total amount, and is preferably, for example, 10 mass% or less of the total amount of thermoelectric conversion material and sintering aid, and more preferably 0.01 mass% or more and 2 mass% or less.
[0020] Next, the sintering step shown in FIG. 4 will be described. To obtain a dense bulk by solid-phase reaction, the mixture is placed in a mold for pressure sintering and subjected to pressure heat treatment (S3-2: sintering process), or the mixture is molded into a green compact by uniaxial pressing or CIP (Cold Isostatic Pressing) (S3-1: preforming) and then heat-treated (S3-2: sintering process) to sinter it, thereby obtaining a skutterudite thermoelectric conversion element. By using a sintering aid, it is possible to increase the density by pressure sintering at 45 MPa or less, or even by sintering without pressure, when the mold is enlarged using a device with the same pressing capacity, that is, when the force applied to the surface is constant and the area becomes large and the force per unit area becomes small. As a result, when the density of the sintered body obtained by pressure heat treatment of 50 MPa or more is used as the standard for a thermoelectric conversion element, the relative density can be obtained by sintering without pressure at 90% or more, and by pressure heat treatment of about 10 MPa at 97% or more. For example, it is possible to increase the density even at pressures of 35 MPa or less, 15 MPa or less, or even 10 MPa or less. In this case, the power factor is, for example, Yb 0.3 Co4Sb 12 Regarding the sintering efficiency, if 0.05 to 2 mass% of sintering aid is added and the sintering is heat-treated under pressure of about 10 MPa, the sintering efficiency is 5 mW m at 500°C. -1 ·K -2 With the above, a preferable value can be obtained. The sintering temperature is preferably in the range of 550°C to 860°C. If the temperature is 550°C or higher, sintering can be easily carried out, and if the temperature is 860°C or lower, decomposition of skutterudite can be easily suppressed. The atmosphere is preferably non-oxidizing, and an inert gas (argon Ar, nitrogen N2, etc.) or a vacuum can be used. Reducing hydrogen can also be used. In the following examples, the obtained sintered body was processed into an evaluation size using a slicer or the like and used for evaluation. EXAMPLES
[0021] [Example 1] Assuming that MnSb was used as a sintering aid, manganese (Kojundo Kagaku, 3N, particle size 300μm or less) and antimony (Nihon Seiko, 4N, granular) were weighed out so that the atomic ratio (Mn / Sb) = 1. The weighed raw materials were placed in a carbon crucible and heated and melted in an argon atmosphere in a high-frequency melting furnace. After confirming that the molten metal was stirred by high-frequency waves, the molten metal was poured into a mold. The ingot that had solidified in the mold was set in a liquid quenching and solidification device and melted again in an argon atmosphere. The molten metal temperature was measured with a radiation thermometer and set to 1100°C, after which the molten metal was sprayed onto a rotating copper roll for quenching and solidification, and a ribbon-shaped material was obtained. The ribbon-shaped material was finely pulverized with a crusher (blade mill) to obtain a sintering aid (MnSb fine powder). When this sintering aid powder was measured by XRD, it was found that the compound consisting of Mn and Sb was Mn 1.1 A peak corresponding to a single phase of Sb was obtained.
[0022] Thermoelectric conversion material Yb 0.3 Co4Sb 12 The pure metals Yb, Co, and Sb were weighed according to the composition formula. The weighed pure metal raw materials were placed in a carbon crucible and heated and melted in a high-frequency melting furnace in an inert gas atmosphere. After confirming that the molten metal was stirred by high frequency, the molten metal was poured into a mold. The ingot solidified in the mold was set in a liquid quenching and solidification device and melted again in an inert atmosphere. The molten metal temperature was measured with a radiation thermometer and set to 1150°C, after which the molten metal was sprayed onto a rotating copper roll for quenching and solidification. The quenched and solidified material was heat treated at 700°C for 24 hours in an inert atmosphere and then pulverized using a hammer mill. This resulted in the production of a powder of a thermoelectric conversion material (skutterudite powder). The above-mentioned MnSb fine powder was added to the skutterudite powder in an amount of 1 mass% relative to the total amount, and the mixture was rotated and mixed 1500 times using a mix rotor. 20 g of the mixed powder was placed in a carbon mold with an inner diameter of Φ30 mm and held for 1 hour at 700°C under an argon atmosphere and a press pressure of 15 MPa. In other words, the mixture was placed in a mold for pressure sintering and sintered while being pressed. Apparent density: 7.74 Mg / m 3 A dense sintered body was obtained. The apparent density was determined by the Archimedes method. When the inside of the sintered body was observed with an SEM, it was found to be a dense bulk body, as shown in Figure 6. The obtained sintered body was machined for measurement, and the thermoelectric properties were measured using an Advance Riko ZEM-3. The results are shown in Figure 5. According to Figure 5, at 300°C, the Seebeck coefficient was -158μV / K, the electrical resistivity was 4.69μΩm, and the power factor was 5.29mW m. -1 ·K -2 At 400°C, the Seebeck coefficient is -168μV / K, the electrical resistivity is 5.09μΩm, and the power factor is 5.55mW m -1 ·K -2 At 500°C, the Seebeck coefficient is -175μV / K, the electrical resistivity is 5.48μΩm, and the power factor is 5.60mW m -1 ·K -2 As a result, the resistance was low and the power factor was high compared to Comparative Example 1 described later.
[0023] [Comparative Example 1] A sintered body was produced and evaluated in the same manner as in Example 1, except that no sintering aid was added. The apparent density of this sintered body, as determined by the Archimedes method, was 7.45 Mg / m 3 When the cross section of the sintered body was observed with an SEM, voids were found to exist throughout the material, as shown in Figure 7. The obtained sintered body was machined for measurement, and the thermoelectric properties were measured using an Advance Riko ZEM-3. The results are shown in Figure 5. According to Figure 5, at 300°C, the Seebeck coefficient was -154μV / K, the electrical resistivity was 7.19μΩm, and the power factor was 3.29mW m. -1 ·K -2 At 400°C, the Seebeck coefficient is -165μV / K, the electrical resistivity is 7.84μΩm, and the power factor is 3.46mW m. -1 ·K -2 At 500°C, the Seebeck coefficient is -176μV / K, the electrical resistivity is 8.49μΩm, and the power factor is 3.63mW m. -1 ·K -2 It became.
[0024] [Example 2] As in Example 1, the sintering aid MnSb fine powder and the thermoelectric conversion material Yb 0.3 Co4Sb 12Skutterudite powder was prepared and mixed. Sintering was carried out in the same manner as in Example 1, except that the pressing pressure was kept at 10 MPa for 1 hour. The apparent density of this sintered body measured by the Archimedes method was 7.70 Mg / m 3 When the inside of the sintered body was observed with an SEM, it was found to be a dense bulk body. The obtained sintered body was machined for measurement, and its thermoelectric properties were measured using an Advance Riko ZEM-3. The results showed a Seebeck coefficient of -158μV / K at 300℃, an electrical resistivity of 5.31μΩm, and a power factor of 4.68mW m -1 ·K -2 At 400°C, the Seebeck coefficient is -168μV / K, the electrical resistivity is 5.76μΩm, and the power factor is 4.92mW m -1 ·K -2 At 500°C, the Seebeck coefficient is -176μV / K, the electrical resistivity is 6.06μΩm, and the power factor is 5.11mW m -1 ·K -2 As a result, compared with Comparative Example 1, the resistance was low and the power factor was high.
[0025] [Example 3] Manganese and antimony were weighed out as sintering aids so that the Mn / Sb atomic ratio was 1.8, and the subsequent process was the same as in Example 1 to produce a powder of the sintering aid. When this sintering aid was measured by XRD, Mn 1.1 It was found to be a mixture of Sb and Mn2Sb. 0.3 Co4Sb 12 The skutterudite powder was produced by the same process as in the example. Yb 0.3 Co4Sb 121 mass% of MnSb fine powder was added to the skutterudite powder and mixed in a mortar. 2 g of the mixed powder was placed in a die with an inner diameter of Φ10 mm and pressure molded at room temperature with a uniaxial press at 15 kN. The molded body was placed in a vacuum-compatible furnace, heated at a rate of 35°C / min at a vacuum of less than 10 Pa, and then held at 730°C for 1 hour. In other words, the mixture was placed in a mold for molding, pressure molded, and then sintered in a vacuum without pressure. The pre-sintered molded body had a diameter of Φ10 mm, but after heat treatment, i.e., sintering, it shrank by 10% to Φ8.97 mm, and its apparent density by Archimedes' method was 7.52 Mg / m 3 SEM observation revealed that sintering had progressed, as shown in Figure 8(a). From the above examples, it is possible to obtain a strength of 7.50 Mg / m without applying pressure. 3 7.70Mg / m at pressures of 15MPa or less 3 It was found that the above density could be obtained.
[0026] [Comparative Example 2] Using the same batch of skutterudite powder used in Example 3, 2 g of the skutterudite powder was placed in a die with an inner diameter of Φ10 mm and pressure molded at room temperature with a uniaxial press at 15 kN. The molded body was placed in a vacuum-compatible furnace, and the temperature was increased at 35°C / min at a vacuum degree of less than 10 Pa, and then held at 730°C for 1 hour. The diameter of the sample after heat treatment was Φ10 mm, the same as before heat treatment. When the structure was observed with an SEM, it was observed that the skutterudite powder was still unsintered, as shown in Figure 8(b).
[0027] [Example 4] Skutterudite powder and MnSb fine powder were prepared using the same process as in Examples 1 and 2, and Fig. 9 shows the change in density of the sintered body when the sintering pressure was changed in the range of 10 MPa to 68 MPa. Pressure sintering at 68 MPa is taken as a reference example. According to this, in the low pressure range of 5 MPa to 35 MPa, the density is higher than the comparative example (no sintering aid added), and the apparent density at 68 MPa pressure sintering is 7.77 Mg / m 3When compared to a sintered body sintered at 68 MPa, the relative density remains at 99% or more even when the pressure is reduced to 10 MPa. This shows that densification is easy even with low-pressure sintering, making it suitable for mass production.
[0028] [Example 5] In each condition of Example 2, the sintering aid was 0.1 mass%. The density at this time was 7.71 Mg / m 3 (relative density 99% when the 68 MPa pressure sintered compact of the reference example is used as the standard). The results are shown in Fig. 9. According to this, the density is higher than that of Comparative Example 2, and from this, it was found that even when the amount of sintering aid is small, for example, densification is easy even by low-pressure pressure sintering, and mass productivity is high.
[0029] 10, a 70 nm line analysis was performed across the grain boundaries using HAADF-STEM-EDX (High-angle Annular Dark Field Scanning TEM Energy dispersive X-ray spectroscopy) near the grain boundaries in Example 3. This revealed that the Mn concentration at the grain boundaries tends to be three times higher than near the grain boundaries.
[0030] [Example 6] A skutterudite powder and MnSb fine powder were prepared in the same process as in Example 1, and a mixed powder was produced by mixing the powder with 0.05 mass% MnSb added, and sintered at a pressure of 10 MPa. The density of the sintered body was 7.70 Mg / m 3 When the pressure-sintered compact at 68 MPa without the addition of sintering aid shown in Example 4 or FIG. 9 is used as a reference, the relative density is 99%, and the density is the same as that of the pressure-sintered compact at 10 MPa with 1 mass% of sintering aid added in Example 4, so it was found that even when the amount of sintering aid added was 0.05 mass%, the densification effect was comparable to that of the addition of 1 mass%. The thermoelectric properties of the obtained sintered body were measured in the same manner as in Example 1 and Comparative Example 1. The Seebeck coefficient at 300°C was -160 μV / K, the electrical resistivity was 4.93 μΩm, and the power factor was 5.16 mW m -1·K -2 At 400°C, the Seebeck coefficient is -171μV / K, the electrical resistivity is 5.39μΩm, and the power factor is 5.39mW m -1 ·K -2 At 500°C, the Seebeck coefficient is -179μV / K, the electrical resistivity is 5.76μΩm, and the power factor is 5.59mW m -1 ·K -2 As a result, compared with Comparative Example 1, the resistance was low and the power factor was high.
[0031] [Example 7] A skutterudite powder and MnSb fine powder as a sintering aid were prepared in the same process as in Example 1, and a mixed powder was produced by mixing the powder with 1.5 mass% MnSb added, and sintering was performed at a pressure of 5 MPa. The density of the sintered body was 7.54 Mg / m 3 A higher density was obtained than in Comparative Example 3, and it was found that the density was increased by adding MnSb fine powder.
[0032] [Comparative Example 3] A sintered body was produced at a sintering pressure of 5 MPa in the same manner as in Example 7, except that no sintering aid was added. The density was measured and found to be 7.08 Mg / m 3 It was.
[0033] [Example 8] A sintered body was produced in the same process as in Example 7, except that the sintering pressure was 3 MPa. The density was measured and found to be 7.36 Mg / m 3 Although the sintering pressure was lower than that of Comparative Example 3, the density was higher, and it was found that the density was increased by adding a sintering aid.
[0034] [Example 9] As a sintering aid, manganese and antimony were weighed out so that the atomic ratio Mn / Sb was 0.606, and the subsequent process was the same as in Example 1 to produce a powder of the sintering aid. When this sintering aid was measured by XRD, Mn 1.1 It was found to be a mixture of Sb and Yb 0.3 Co4Sb 12The skutterudite powder was prepared by the same process as in Example 1. As in Example 7, a mixed powder was prepared by adding 1.5 mass% of sintering aid powder, and sintering was performed at a pressure of 5 MPa. The density of the sintered body was 7.57 Mg / m 3 A higher density was obtained than in Comparative Example 3. 1.1 It was found that the addition of a sintering aid, a mixture of Sb and Sb, increased the density.
[0035] [Example 10] Thermoelectric conversion material Ce 0.2 (Co 3.95 Mn 0.05 )Sb 12 Pure metals Ce, Co, Mn, and Sb were weighed according to the composition formula, and then skutterudite powder was produced in the same process as in Example 1. Sintering aid MnSb fine powder (Mn by XRD) 1.1 The preparation of the skutterudite powder and the MnSb fine powder was carried out in the same manner as in Example 1. When this mixed powder was used and the sintering pressure was varied in the range of 8.5 MPa to 45 MPa, the density of the sintered body was 7.67 Mg / m at 45 MPa. 3 , and 7.64 Mg / m at 30 MPa. 3 , and 7.58 Mg / m at 8.5 MPa. 3 The change in density versus pressure sintering pressure is shown in Figure 11. Pressure sintering at 70 MPa without the addition of sintering aids is taken as a reference example. According to this, in the low pressure range of 8.5 MPa to 45 MPa, the density is higher than that of the sintered body without the addition of sintering aids, and the density of the sintered body sintered under pressure at 70 MPa (reference example) is 7.66 Mg / m 3 On the other hand, even when the sintering pressure was reduced to 8.5 MPa, the relative density of the sintered body containing the sintering aid MnSb fine powder was as high as 99%. From this, it can be seen that the relative density of the sintered body was 7.50 Mg / m 3 It was found that the above density could be obtained.
[0036] [Comparative Example 4] The same procedure as in Example 10 was used except that no sintering aid was added. The sintering pressure was varied in the range of 8.5 MPa to 45 MPa, and the results are shown in Figure 11. The density of the sintered body was 7.64 Mg / m at 45 MPa. 3 , 7.58 Mg / m at 30 MPa 3 , 7.50 Mg / m at 15 MPa 3 At 8.5 MPa, the density was 7.39 MPa. At both sintering pressures, Example 10 had a higher density, confirming the effect of the sintering aid in promoting sintering.
[0037] [Example 11] According to the composition formula of the thermoelectric conversion material CoSb3, pure metal Co and Sb were weighed, and then skutterudite powder was produced in the same process as in Example 1. The sintering aid MnSb fine powder (Mn by XRD) was 1.1 The preparation of the skutterudite powder and the MnSb fine powder (1 mass % MnSb fine powder) was carried out in the same manner as in Example 1. This mixed powder was pressure sintered at a press pressure of 10 MPa, but otherwise the same conditions were used as in Example 1. The apparent density of the sintered body measured by the Archimedes method was 7.56 Mg / m 3 As a reference example, pressure sintering at 68 MPa without adding sintering aids resulted in a density of 7.60 Mg / m 3 According to this, even at a low pressure of 10 MPa, by adding a sintering aid, the relative density was 99% and the density was high when the sintered body at 68 MPa was used as a reference. The density was also higher than that of the 10 MPa sintered body in Comparative Example 5 (no sintering aid added) described later. The results are shown in FIG.
[0038] [Comparative Example 5] The results of pressure sintering were shown in Figure 12, where the pressure during sintering was changed in the range of 5 MPa to 45 MPa in the same manner as in Example 11, except that no sintering aid was added. The density was 7.57 Mg / m at 45 MPa. 3 , 7.45 Mg / m at 30 MPa 3 , and 7.33 Mg / m at 15 MPa. 3 , 7.23 Mg / m at 10 MPa 3At 45 MPa, the density was equivalent to that of Example 11, and at sintering pressures of 30 MPa or less, Example 11 had a higher density, confirming the sintering promotion effect of the sintering aid.
[0039] [Example 12] For comparison with 5 MPa pressure sintering in Comparative Example 5 (no sintering aid added), fine powder of sintering aid prepared by compounding CoSb3 skutterudite powder with an atomic ratio of Mn / Sb=2 was added and sintered at 5 MPa. This fine powder of sintering aid was prepared by the same process as in Example 1 and mixed with the skutterudite powder to make 1.5 mass%. The density of the sintered body was 7.40 Mg / m 3 A higher density was obtained than the compact sintered under pressure at 5 MPa shown in Comparative Example 5.
[0040] [Example 13] The mixed powder produced by the same process as in Example 11 (mixing the MnSb fine powder with the thermoelectric material CoSb3 skutterudite powder so that the content was 1 mass%) was pressure sintered at 600°C under a pressure of 68 MPa. The conditions other than the temperature and pressure were the same as in Example 11. The density of the sintered body was 7.57 Mg / m 3 In comparison with Comparative Example 6, i.e., the result without adding the MnSb sintering aid, a sintered body with a higher density was obtained. In addition, in comparison with the sintering at 700°C and 68 MPa described in Example 11, a high density of 100% was obtained in terms of relative density, even though the sintering temperature was lowered from 700°C to 600°C.
[0041] [Comparative Example 6] A sintered body was produced in the same manner as in Example 13, except that no sintering aid was added, and the density was measured and found to be 7.40 Mg / m 3 The density was lower than that of the sample containing the sintering aid.
[0042] [Example 14] Mn, a sintering aid 1.1 Sb fine powder was prepared by the same process as in Example 1. Next, the thermoelectric conversion material Ce1 (Fe 3.925 Mn 0.075 )Sb 12The pure metals Ce, Fe, Mn, and Sb were weighed according to the composition formula. The weighed pure metal raw materials were placed in a carbon crucible and heated and melted in a high-frequency melting furnace in an inert gas atmosphere. After confirming that the molten metal was stirred by high-frequency, the molten metal was poured into a mold. The ingot solidified in the mold was set in a liquid quenching and solidification device and melted again in an inert atmosphere. The molten metal temperature was measured with a radiation thermometer and set to 1100°C, after which it was rapidly solidified by spraying the molten metal onto a rotating copper roll. The rapidly solidified material was heat-treated at 660°C for 24 hours in an inert atmosphere and then pulverized using a hammer mill. This resulted in the production of a thermoelectric conversion material powder (skutterudite powder). In the skutterudite powder, Mn 1.1 Sb fine powder was added and mixed so that the content was 0.8 mass% of the total amount. Sintered bodies were produced by pressure sintering at a sintering temperature of 660°C and five pressure conditions of 3 MPa, 5 MPa, 7.5 MPa, 10 MPa, and 15 MPa. The other sintering conditions were the same as in Example 1. The density of the sintered body was 7.67 Mg / m at a press pressure of 3 MPa. 3 , and 7.83 Mg / m at 5 MPa. 3 , 7.84 Mg / m at 7.5 MPa 3 , 7.84 Mg / m at 10 MPa 3 , 7.85 Mg / m at 15 MPa 3 As a reference example, when sintering was performed in the same manner without adding sintering aids and at a press pressure of 68 MPa, the yield was 7.86 Mg / m 3 According to this, when the pressure sintered body was sintered at 68 MPa, the relative density was 98% when sintered at 3 MPa and 100% when sintered at 5 MPa, and the density was equivalent to that of high pressure sintering even at low pressure. Also, compared to Comparative Example 7 (no sintering aid added), the density was higher when sintered at low pressure of 7.5 MPa or less with the addition of sintering aid.
[0043] The 3 MPa pressure sintered compact was machined for measurement purposes, and its thermoelectric properties were measured using an Advance Riko ZEM-3. The results showed a Seebeck coefficient of 140 μV / K, electrical resistivity of 6.67 μΩm, and power factor of 2.92 mW m at 300°C. -1 ·K -2At 400°C, the Seebeck coefficient was 152 μV / K, the electrical resistivity was 7.18 μΩm, and the power factor was 3.23 mW m -1 ·K -2 At 500°C, the Seebeck coefficient was 162 μV / K, the electrical resistivity was 7.64 μΩm, and the power factor was 3.43 mW m -1 ·K -2 As a result, the sample exhibited a low electrical resistance and a high power factor compared to Comparative Example 7 described below.
[0044] [Comparative Example 7] A sintered body was produced and evaluated in the same manner as in Example 14, except that no sintering aid was added and the pressing pressure during sintering was changed. The density of the sintered body was 7.57 Mg / m at a pressing pressure of 3 MPa. 3 , and 7.76 Mg / m at 5 MPa. 3 , and 7.81 Mg / m at 7.5 MPa. 3 , 7.85 Mg / m at 10 MPa 3 , 7.85 Mg / m at 15 MPa 3 It was. The 3 MPa pressurized sintered body was machined for measurement, and the thermoelectric properties were measured using an Advance Riko ZEM-3. The sample fabricated at a press pressure of 3 MPa had a Seebeck coefficient of 137 μV / K, electrical resistivity of 7.83 μΩm, and power factor of 2.39 mW m at 300°C. -1 ·K -2 At 400°C, the Seebeck coefficient is 149μV / K, the electrical resistivity is 8.44μΩm, and the power factor is 2.64mW m -1 ·K -2 At 500°C, the Seebeck coefficient is 157μV / K, the electrical resistivity is 8.93μΩm, and the power factor is 2.76mW m. -1 ·K -2 It became.
Claims
1. A step of mixing a powder of a skutterudite-type thermoelectric conversion material containing Sb with a sintering aid containing a compound of Mn and Sb to obtain a mixture; sintering the mixture; and A method for producing a thermoelectric conversion element, comprising:
2. The compound of Mn and Sb is found by XRD to be Mn 1.1 Sb or Mn 2 2. The method for producing a thermoelectric conversion element according to claim 1, wherein a peak of at least one of the crystal structures of Sb is observed.
3. 3. The method for producing a thermoelectric conversion element according to claim 1, wherein the mixture contains 10 mass % or less of the sintering aid with respect to the total amount of the thermoelectric conversion material and the sintering aid.
4. 4. The method for manufacturing a thermoelectric conversion element according to claim 1, wherein the thermoelectric conversion material powder contains Yb and Co.
5. 4. The method for manufacturing a thermoelectric conversion element according to claim 1, wherein the thermoelectric conversion material powder contains Ce and Fe.
Citation Information
Patent Citations
Fe-base sintered magnetic core material and its production
JP1991068743A
Production method for sintered body
JP2005200249A
Thermoelectric material and method for producing same
WO2004049464A1
Skutterudite thermoelectric materials of hole-compensated type and method of making the same
WO2013009430A1
Tin-oxide refractory and manufacturing method therefor
WO2013100074A1